Numerical study on mean flow characteristics for a combined turbulent wall and offset jets with a parallel co-flow. Issue 1 (31st December 2022) - Hnaien, Nidhal; Mondal, Tanmoy; Ajmi, Mariem; Marzouk, Saloua; Aich, Walid; Kolsi, Lioua
Abstract : Combined turbulent wall and offset jets with and without the presence of a parallel co-flow stream are investigated using the k-ω turbulence model. We focus on the effects of co-flow velocity on the locations of various characteristic points formed owing to the interaction of wall and offset jets in the dual jet flow. The inlet Reynolds number is taken as 15, 000 and the offset ratio is varied from 5 to 11. At low offset ratios, the co-flow velocity effect remains almost negligible. With the progressive increase in co-flow velocity, the characteristic points are gradually relocated towards the further downstream direction with a transverse movement away from the bottom wall whose effect is weakened with the increase in co-flow velocity. Furthermore, regression analysis shows power law and linear correlations of the longitudinal and transverse coordinates of characteristic points with the co-flow velocity and the offset ratio.